2004
DOI: 10.1111/j.1365-294x.2004.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

Group‐specific polymerase chain reaction for DNA‐based analysis of species diversity and identity in dietary samples

Abstract: Unique DNA sequences are present in all species and can be used as biomarkers for the detection of cells from that species. These DNA sequences can most easily be detected using the polymerase chain reaction (PCR), which allows very small quantities of target DNA sequence to be amplified even when the target is mixed with large amounts of nontarget DNA. PCR amplification of DNA markers that are present in a wide range of species has proven very useful for studies of species diversity in environmental samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
177
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(178 citation statements)
references
References 44 publications
1
177
0
Order By: Relevance
“…The nearest relatives of the Streptophyta sequences included not only marine sequences but also genes from higher plants, suggesting potential contamination. However, reports of similar sequences from whale faeces (Jarman et al 2004) and guts of lobster larvae (Suzuki et al 2006) indicate that they represent hitherto unknown organisms in marine plankton. Similarly, some of the fungal sequences were related to sequences obtained from marine plankton.…”
Section: Resultsmentioning
confidence: 99%
“…The nearest relatives of the Streptophyta sequences included not only marine sequences but also genes from higher plants, suggesting potential contamination. However, reports of similar sequences from whale faeces (Jarman et al 2004) and guts of lobster larvae (Suzuki et al 2006) indicate that they represent hitherto unknown organisms in marine plankton. Similarly, some of the fungal sequences were related to sequences obtained from marine plankton.…”
Section: Resultsmentioning
confidence: 99%
“…Although this is not an issue for species with highly specialised diets (Rougerie et al, 2011), this is particularly limiting for generalist predators that feed on a variety of prey species. Until recently, such mixed DNA samples could be analysed only after the development of large panels of species-specific primers (Jarman et al, 2004) used in complex multiplex PCRs (Harper et al, 2005;King et al, 2011) or cloning analyses (Zeale et al, 2011).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…These approaches include (1) stable isotope ratios and fatty acid signatures as biomarkers of assimilated food (Hobson and Welch 1992;Graeve et al 2001;Nyssen et al 2002), and (2) the nascent approach of using universal polymerase chain reaction (PCR) primers to amplify and sequence the DNA from gut contents to identify ingested organisms (Blankenship and Yayanos 2005). Consumed organisms that are digested beyond visually identifiable remains can still leave residual DNA in the digestive tract (Duplessis et al 2004;Jarman et al 2004). Recently, it was shown that this dietary DNA can be amplified with highly conserved primers and sequenced (see Blankenship and Yayanos 2005).…”
mentioning
confidence: 99%